Exploring the Edges of Sacramentality: Liturgy between the Reality of Life and the Truth of Faith. (September 2018) - Pott, Thomas
The Church1 is represented in the Holy Mysteries, not in figure only but as the limbs are represented in the heart, the branches in the root, and, as our Lord has said, the shoots in the vine. For here is no mere sharing of a name or analogy by resemblance, but an identity of actuality.